Comparison of Plasma NPY and Zinc Levels of Elite Weightlifters and Sedentaries - İribalcı, Şükran; Akkus, Hasan; Halifeoglu, Ihsan; Baltaci, Abdulkerim Kasim (My University, 2021)
Neuropeptide Y (NPY), a strong stimulant of nutrition, and zinc, which has an important effect on nutrition regulation, have attracted the attention of many researchers. The aim of this study was to investigate the relationship between plasma NPY and zinc levels in elite weightlifters. Thirty healthy subjects between the ages of 18-27 participated in the study voluntarily. The subjects were composed of two equal groups: the control group who did not exercise regularly and the elite weightlifters who did regular training. Plasma NPY (ELISA) and zinc levels (Atomic Absorption Spectrophotometer) were determined in blood samples collected from subjects. When serum NPY and zinc values were compared between the groups, it was found that NPY levels of elite weightlifters were higher than controls (p <0.01) and zinc levels were lower (p <0.01). The findings of the study show that physical activity leads to changes in NPY and zinc release. As a result, there may be a critical relationship between these changes and physical performance.
Keywords: Zinc; NPY; Elite Weightlifter; Sedentary